Extrafollicular AOT presenting as a gingival overgrowth: A rare case report - Preeti Patil; Kirty Nandimath; Krishna Burde; Karthik J Kabbur (Wolters Kluwer Medknow Publications, 2020)
Adenomatoid odontogenic tumor (AOT) is an uncommon, benign, asymptomatic, slow-growing tumor with marked predilection for occurrence in the anterior maxilla. It represents 3% of all odontogenic tumors. There are three clinicopathological variants of AOT, namely, follicular, extrafollicular, and peripheral. This paper describes in detail a rare case of an extrafollicular adenomatoid odontogenic tumor occurring in mandible and presenting as gingival growth.